Momentos articulares durante a marcha de hemiplégicos pós-acidente vascular encefálico - Rossato, Carla Emilia (2015)
People who have suffered stroke often have difficulty during walking. One of the reasons is hemiplegia, which is the main motor impairment caused by stroke. Hemiplegia generates asymmeries in limb control that often can result in compensation and overload in one of the hemisphere, leaving individuals susceptible to joint moments and/or exaggerated in both affected and unaffected limbs. The objective of this study was to analyze joint mechanics during hemiplegic gait, post-stroke. The sample was composed of 28 hemiplegic subjects and 22 subjects without hemiplegia. Kinetic and kinematic gait magnitudes were obtained for subsequent calculation of joint moments via inverse dynamics method. The hemiplegic individuals were divided into two groups: fast group and slow group, according to their self selected speed adopted during the data collection, and subjects without hemiplegia took part of the third group. Comparisons were conducted between groups and between the affected and unaffected members in the hemiplegic group. The results showed similar joint moments patterns between hemiplegic individuals and subjects without hemiplegia. Nevertheless, a higher number of differences were found in joint moments between groups and it became more evident at the beginning of the stance phase. Few differences were found on comparisons between the affected and unaffected limbs within the hemiplegic group. We concluded that people who have suffered strokes are susceptible to changes in joint moments, being more evident in hemiplegic individuals who adopted a faster walking speed. It occurs because the walking speed is an intervening factor for the calculation of joint moments.